SOSIALISASI SISTEM ASURANSI KESEHATAN: MENINGKATKAN KESADARAN DAN AKSES MASYARAKAT DESA - Toar. W. J. Hatibie; Christiawati Sapii; Delan Isa (LPPM Universitas Bina Mandiri Gorontalo, 2022)
The purpose of this community service is so that residents of Keramat Village can understand the health insurance system. The method used in this community service is to first conduct a survey on the insurance system that has been implemented in the village, after which a socialization was prepared for the community in Kramat Village which was carried out offline, on September 22, 2022 with 30 participants. After that, a lecture was held with the help of media in the form of powerpoint, questionnaires and a discussion and question and answer session. The distribution of this questionnaire was to measure community knowledge before and after the socialization was carried out. Based on the findings, there are still many people who do not fully understand how the insurance system works.